Potensi Desa Doulu dalam Pengembangan Desa Wisata di Kabupaten Karo, Sumatera Utara - Haris Sutan Lubis; Samerdanta Sinulingga; Arwina Sufika; Noercahaya Bangun (Fakultas Pariwisata Universitas Pancasila, 2014)
This article explains the results of a preliminary study on tourism resources conducted in one of tourism villages in Karo Regency, North Sumatra. The study describes nature-based and cultural tourism resources in the village, while also identifies various tourism activities that can be developed according to these resources. This study also tries to assess issues that need to be addressed if tourism is to be developed in the village. These issues relate to the roles of major stakeholders, such as the communities, local government, private sector or the tourism industry, and relevant NGOs. It is concluded that cooperations between stakeholders need to be established and each party should enhance its role in developing tourism in the village.